The prominent role of the S100A8/S100A9-CD147 axis in the progression of penile cancer - Mohr, Tobias; Zwick, Anabel; Hans, Muriel Charlotte; Bley, Isabelle Ariane; Braun, Felix Leon; Khalmurzaev, Oybek; Matveev, Vsevolod Borisovich; Loertzer, Philine; Pryalukhin, Alexey; Hartmann, Arndt; Geppert, Carol-Immanuel; Loertzer, Hagen; et al. (Frontiers in Oncology, 2022)
Currently, no established biomarkers are recommended for the routine diagnosis of penile carcinoma (PeCa). The rising incidence of this human papillomavirus (HPV)-related cancer entity highlights the need for promising candidates. The Calprotectin subunits S100A8 and S100A9 mark myeloid-derived suppressor cells in other HPV-related entities while their receptor CD147 was discussed to identify PeCa patients at higher risk for poor prognoses and treatment failure. We thus examined their expression using immunohistochemistry staining of PeCa specimens on tissue microarrays (TMA) of the tumor center, the invasion front and lymph node metastases. Notably, while the tumor center was significantly more intensively stained than the invasion front, lymph node metastases were thoroughly positive for both S100 subunits. An HPV-positive status combined with an S100A8+S100A9+ profile related with an elevated risk for metastases. We observed several PeCa specimens with S100A8+S100A9+ infiltrating immune cells overlapping with CD15 marking neutrophils. The S100A8+S100A9+CD15+ profile was associated with dedifferentiated and metastasizing PeCa, predominantly of HPV-associated subtype. These data suggest a contribution of neutrophil-derived suppressor cells to the progression of HPV-driven penile carcinogenesis. CD147 was elevated expressed in PeCa specimens, prominently at the tumor center and in HPV-positive PeCa cell lines. CD147+HPV+ PeCa specimens were with the higher frequency metastasizing cancers. Moreover, an elevated expression of CD147 of HPV-positive PeCa cell lines correlated negatively with the susceptibility to IgA-based neutrophil-mediated tumor cell killing. Finally, stratifying patients regarding their HPV/S100A8/S100A9/CD15/CD147 profile may help identify patients with progressing cancer and tailor immunotherapeutic treatment strategies.